Secondhand Smoke Exposure Among High-Risk Patients in the United States (NHANES 2001–2012): Implications for Clinical Practice. Issue 4 (23rd March 2018) - Asfar, Tahgrid; Koru-Sengul, Tulay; Ruano-Herreria, Estefania C; Sierra, Danielle; Lee, David J; Arheart, Kristopher L
Abstract: Introduction: Patients with cancer, cardiovascular disease (CVD), and respiratory disease are susceptible to health consequences related to secondhand smoke (SHS) exposure. This study examined the prevalence, time trends, and correlates of SHS exposure among these patients compared with individuals without these diseases (control). Methods: Data were obtained from the 2001–2012 National Health and Nutrition Examination Survey. All adults (≥20 years old) who were nonsmokers and exposed to SHS (serum cotinine level 0.015–10 ng/mL), had cancer ( n = 1, 440), CVD (congestive heart failure, coronary heart disease, angina, heart attack, or stroke; n = 1, 754), respiratory disease (asthma, chronic bronchitis, emphysema; n = 1, 444), or none of these diseases (control; n = 11, 615) were included in the analysis. Weighted prevalence, weighted second-degree polynomial linear regression of prevalence on year for trend analysis, and multivariable logistic regression analyses were performed with adjustments to the complex survey design. Results: SHS exposure was the highest among patients with respiratory disease (72.1%), followed by patients with CVD (70.6%), controls (70.4%), and patients with cancer (65.4%). From 2001 to 2012, exposure decreased the most among CVD patients (19.6%), followed by controls (16.0%), cancer patients (14.7%), and respiratory patients (10.0%). Exposed individuals in all groups were more likely to be younger, Black, and less educated. Exposed patients with respiratory disease were more likely to be former smokers ( p < .05 for all). Conclusions: SHS exposure among these patients is high and comparable to the general population. Strengthening smoke-free policies in all settings is critical. More efforts are needed to address SHS exposure more effectively in clinical care settings. Implications: Despite the negative health effect of SHS exposure among patients with cancer, CVD, and respiratory disease, modest progress has been made in reducing their exposure. Continued efforts to strengthen smoke-free policies in workplaces, public place, and multiunit housing is critical. In addition, exposure to SHS among these patients seems to be overlooked in clinical care settings. More efforts are needed to address this problem more effectively in health care settings and investigate specific interventions directed at increasing patients' awareness about the risk of exposure to SHS and helping them to reducing their exposure.